Polymedia on Working Mothers with Long Distance Marriage - Putri, Dian Widya; Yulianti, Yulianti -; Hamdan, Stephani Raihana (MediaTor (Jurnal Komunikasi), 2022)
People in this cyber era use various media to carry out all kinds of communication. the concept of polymedia sees how a person navigates and manages so many media according to their interpersonal communication needs. This study looks at the application of the polymedia concept to working mothers who experience Long Distance Marriage (LDM). The research method is descriptive qualitative with data collection techniques through interviews and observations. The informants in this study are working mothers who have a long-distance marriages. The results of this study in the polymedia contour section found that the informants develop the use of media by updating and combining several media. The most favorite or frequently used media are those with full features and low cost. The level of accessibility, affordability, and media literacy of informants varied but tended to move in a better direction. The results from the elements of polymedia are that the informants feel that the media can convey affection, feelings, and emotions in interpersonal communication with their families. In the element of remediation, there is a reciprocal relationship that informants choose the media that suits their interpersonal communication needs. Otherwise, technological advances in media have also changed how they communicate. Overall, Flexibility, focus, and adaptability are key for informants to navigate new media and their abundance of interpersonal communication.